A method and sensor for detecting L-glutamic acid based on molecularly imprinted polymer film modified electrode
L-glutamate molecular imprinted polymerization film was prepared by power-on polymerization on glassy carbon electrodes modified by MWCNTs to form an enzyme-free MIP/MWCNTs/GCE sensor, which solved the stability and repetition problems caused by enzyme modification in the prior art. High sensitivity and low cost L-glutamate detection is achieved.
Patent Information
- Application Number
- CN201910531880.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-06-19
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2039-06-19
AI Technical Summary
The existing L-glutamate electrochemical detection methods rely on enzyme modification, resulting in strict usage conditions, poor sensor stability and repeatability, and high cost.
The molecular imprinted polymerization film with L-glutamic acid as the template and 4,6-diaminoresorcinol as the monomer was prepared on a glass carbon electrode modified with multi-walled carbon nanotubes (MWCNTs) to form a non-existent Enzyme molecular blotting sensor MIP/MWCNTs/GCE.
Fast and sensitive detection of L-glutamic acid is achieved, with a detection limit of 5.13×10-9mol/L, with good selectivity, high sensitivity, strong anti-interference ability, and low cost. It is suitable for L-glutamic acid in pig serum Acid detection.
Smart Images

Figure CN110231382B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical / biological sensing, and in particular relates to an L-glutamic acid detection method and a sensor based on a molecular imprinting polymer film modified electrode. Background Art
[0002] L-Glutamic acid (L-Glu), as an acidic non-essential amino acid, has an important impact on the metabolism and control of organisms, the diagnosis and treatment of diseases, and the development of the pharmaceutical and food industries. L-Glu is an important excitatory neurotransmitter in organisms and plays a vital role in brain functions such as learning and memory. For most eukaryotic organisms and mammals, L-Glu can also be used as a nitrogen source to supply energy. In addition, L-Glu is also widely used in the food industry as a flavor enhancer. The normal L-Glu content in the human body cannot exceed 30 mg / kg. Excessive L-Glu intake can lead to certain neurological diseases such as chorea, Parkinson's syndrome, and some allergic reactions such as headaches and stomachaches. Therefore, the rapid and sensitive detection of L-Glu is of great significance for neurological and pathological research and food safety.
[0003] At present, the commonly used detection methods for L-Glu are: colorimetry, fluorescence spectroscopy, capillary electrophoresis, microdialysis, nuclear magnetic resonance spectroscopy, high performance liquid chromatography and high performance liquid chromatography-mass spectrometry, etc. These detection methods have some shortcomings such as expensive instruments, cumbersome sample processing, complex operation, low sensitivity, etc. Compared with them, electrochemical detection methods have the advantages of fast response, high sensitivity, and simple operation. Therefore, the research on electrochemical detection of L-Glu has gradually attracted a lot of attention. Gomes et al. prepared a carbon paste electrode of L-Glu dehydrogenase complex to detect L-Glu, with a detection limit of 0.3mM. Neill et al. compared the effects of gold, platinum, palladium, and glassy carbon as electrode materials on L-Glu detection, laying the foundation for subsequent research. Liang et al. used bacteria to replace traditional enzyme modification on glassy carbon electrodes to make sensors, solving the problem of enzyme fixation, and the detection limit of L-Glu was 2.0μM. However, in order to improve selectivity, traditional L-Glu electrochemical detection involves L-Glu oxidase (GLOx) or L-Glu dehydrogenase (GLdh), which makes the use conditions of the sensor become harsh due to the activity of the enzyme, resulting in poor sensor life and stability, and the repeatability will also decrease, which also increases the cost of the sensor. Therefore, it is necessary to use a new method to prepare enzyme-free sensors without reducing selectivity and stability, and molecular imprinting technology can solve this problem.
[0004] Molecular imprinting technology (MIT) is a method that relies on molecular recognition. It achieves specific detection by binding molecules with the same shape and structure as the template through the three-dimensional structure cavity contained in molecular imprinting polymers (MIPs). This recognition principle is similar to "lock-key", so molecular imprinting is also called "artificial molecular lock". Molecular imprinting sensors are widely used in medical diagnosis, bioanalysis, environmental monitoring and food safety assessment due to their high selectivity and sensitivity, low detection limit, low cost and high automation. Zhao et al. used o-aminophenol as a monomer to prepare a glutamate molecular imprinting sensor with a detection limit of 0.5mmol / L. Anirudhan et al. used itaconic acid as a monomer and prepared a molecular imprinting polymer membrane by organic synthesis to realize the potentiometric detection of sodium glutamate. However, a single molecular imprinting sensor still has some disadvantages, such as uneven site distribution, slow adsorption of the MIP to the detected object and low sensitivity caused by slow binding kinetics. Multi-walled carbon nanotubes (MWCNTs) can enhance the sensitivity of molecular imprinting sensors due to their large specific surface area and unique porous and hollow structure. At present, there is no report on the method of constructing glutamate (L-Glu) molecular imprinting sensor (MIP / MWCNTs / GCE) on MWCNTs modified glassy carbon electrode by electropolymerization using glutamate as template and 4,6-diaminoresorcinol as monomer. Summary of the invention
[0005] The present invention aims to overcome the deficiencies of the prior art and provide a method and a sensor for detecting L-glutamic acid based on a molecular imprinting polymer film modified electrode.
[0006] In order to achieve the above object, the technical solution provided by the present invention is:
[0007] The L-glutamic acid detection method based on molecular imprinting polymer film modified electrode comprises the following steps:
[0008] (1) preparing a MWCNTs dispersion: placing MWCNTs in a NN dimethylformamide solution, and preparing a MWCNTs dispersion after ultrasonic treatment, wherein the concentration of MWCNTs in the MWCNTs dispersion is 0.5 to 2.0 mg / mL;
[0009] (2) preparing an electropolymerization base solution: dissolving 4,6-diaminoresorcinol and L-glutamic acid in a PBS buffer solution at a pH of 4.0 to 5.5, and preparing a mixed liquid of 4,6-diaminoresorcinol and L-glutamic acid, i.e., an electropolymerization base solution, wherein the molar concentration ratio of 4,6-diaminoresorcinol to L-glutamic acid in the electropolymerization base solution is (2 to 6):1, the concentration of the PBS buffer solution in the electropolymerization base solution is 0.01 to 0.20 mol / L, and the preferred pH of the electropolymerization base solution is pH 5.0;
[0010] (3) Preparation of molecular imprinted polymer modified electrode: polishing the surface of glassy carbon electrode, ultrasonic cleaning and air-drying, applying MWCNTs dispersion droplets to the surface of glassy carbon electrode, drying to obtain MWCNTs / GCE, placing MWCNTs / GCE in electropolymerization base solution, scanning in the range of -0.2 to 2.0 V for 20 to 30 cycles by cyclic voltammetry, and then placing the electrode in formic acid / acetonitrile solution for elution for 10 to 20 min to obtain molecular imprinted polymer modified electrode MIP / MWCNTs / GCE; the volume ratio of formic acid to acetonitrile in the formic acid / acetonitrile solution is (0.5 to 4):1;
[0011] (4) A three-electrode system was formed using molecular imprinting polymer film modified electrode MIP / MWCNTs / GCE as the working electrode, a silver / silver chloride electrode as the reference electrode, and a platinum wire electrode as the counter electrode. Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were then used to investigate the electrochemical behavior of L-glutamate on different modified electrodes. Differential pulse voltammetry (DPV) was used to test L-glutamate at different concentrations, and a working standard curve was drawn. The standard addition method was then used to detect L-glutamate in the test samples.
[0012] Preferably, in step (3), the surface of the glassy carbon electrode is polished using 0.3 μm and 0.05 μm alumina powders, respectively.
[0013] Preferably, the diameter of the glassy carbon electrode in step (3) is 3 mm, 5 μL of MWCNTs dispersion is dropwise coated on the surface of the glassy carbon electrode, and MWCNTs / GCE is obtained after drying, and the MWCNTs / GCE is placed in 10 mL of electropolymerization base solution.
[0014] Preferably, in step (4), the concentration of Fe(CN) in the mixture is 2.0 mmol / L. 4- / 3- -0.20mol / L Na2SO4 solution, cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were used to investigate the electrochemical behavior of L-glutamic acid on different modified electrodes; in a potassium ferrocyanide solution prepared by PBS solution, differential pulse voltammetry (DPV) was used to test L-glutamic acid of different concentrations, a working standard curve was drawn, and then the standard addition method was used to detect L-glutamic acid in the sample to be tested; the concentration of the PBS buffer solution for detection was 0.01-0.20mol / L, the pH of the PBS buffer solution for detection was pH3.7-4.4, the preferred pH of the PBS buffer solution for detection was pH4.2, and the concentration of the potassium ferrocyanide solution for detection was 1.0-10.0mmol / L.
[0015] The L-glutamic acid molecular imprinting electrochemical detection sensor based on the molecular imprinting polymer film modified electrode comprises a molecular imprinting polymer film modified electrode as a working electrode; the molecular imprinting polymer film modified electrode comprises a glassy carbon matrix (5), the surface of the glassy carbon matrix (5) is modified with a MWCNTs film layer (6), the MWCNTs film layer (6) is loaded with a MIPs film layer (7), and a L-Glu molecule three-dimensional structure cavity (9) exists on the MIPs film layer (7).
[0016] Preferably, the sensor comprises a glassy carbon matrix (5) having a thickness of 1.0 to 5.0 mm, an acidified MWCNTs film layer (6) having a thickness of 20 to 200 nm, a MIPs film layer (7) having a thickness of 10 to 100 nm, and a L-Glu molecular three-dimensional structure cavity (9) having a diameter of 1 to 10 nm.
[0017] Preferably, the sensor has a good linear relationship with the concentration of L-glutamic acid, and the linear range of detection is 1.00×10 -8 ~1.00×10 -5 mol / L, the detection limit is 5.13×10 -9 mol / L.
[0018] The present invention adopts an electropolymerization method to prepare a glutamate molecular imprinting membrane with L-glutamate (L-Glu) as a template and 4,6-diaminoresorcinol as a monomer on a multi-walled carbon nanotube (MWCNTs) modified glassy carbon electrode (GCE). The template molecules are eluted with a 1:1 formic acid / acetonitrile solution to obtain a glutamate molecular imprinting sensor (MIP / MWCNTs / GCE). The optimized electropolymerization preparation conditions are: template: monomer = 1:4, polymerization cycle number 23, base solution pH 5.0, elution time 13min. The prepared materials and molecular imprinting membranes were characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM) as well as electrochemical methods. The electrochemical properties of different electrodes were studied by differential pulse voltammetry (DPV), and it was found that MIP / MWCNTs / GCE has sensitive recognition characteristics for L-Glu, and when the L-Glu concentration is 1.00×10 -8 ~1.00×10 -5 mol / L, the peak current has a good linear relationship with the concentration (R 2 =0.9923), the detection limit reached 5.13×10 -9 mol / L (S / N=3). The electrode has good selectivity, high sensitivity, and strong anti-interference ability. It can be used to detect L-Glu in pig serum. The results are consistent with those of the high-performance liquid chromatography method, and the recovery rate reaches 97.4% to 105.5%, indicating that this method can provide a new way for the detection of glutamate and has important application prospects in the field of life sciences.
[0019] Compared with the previous sensor for detecting L-Glu, the sensor prepared by the present invention is an enzyme-free sensor with excellent performance, superior linear range and detection limit. The present invention adopts the electropolymerization method, which is simpler and faster. The monomer used increases the template molecule binding site, and increases the electronic conductivity and sensitivity with the help of MWCNTs. The detection limit of glutamate reaches 5.13×10 -9 mol / L, and can be applied to the determination of L-Glu in pig serum. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Schematic diagram of the working structure of the L-glutamate detection sensor based on molecular imprinting polymer film modified electrode;
[0021] Figure 2 Schematic diagram of the preparation and recognition process of the L-glutamate detection sensor based on molecular imprinting polymer film modified electrode;
[0022] Figure 3 Scanning electron microscopy images of MWCNTs (A), NIP / MWCNTs / GCE (B) and MIP / MWCNTs / GCE (C);
[0023] Figure 4 Transmission electron microscopy characterization images of MWCNTs (A), NIP / MWCNTs (B) and MIP / MWCNTs (C);
[0024] Figure 5 :GCE (a), MWCNTs / GCE (b), MIP / MWCNTs / GCE before elution (c), MIP / MWCNTs / GCE after elution (d) at 2.0mmol / L[Fe(CN)] 4- / 3- -Cyclic voltammogram (A) and electrochemical impedance spectroscopy (EIS) diagram in 0.20 mol / L Na2SO4 solution;
[0025] Figure 6 Different electrodes including GCE (a), MWCNTs / GCE (b), NIP / GCE (c), MIP / GCE (d), MIP / MWCNTs / GCE (e) in the presence of 1.000×10 -5 mol / L L-Glu 5.0mmol / L[Fe(CN)] 4- / 3- -Differential pulse voltammogram in 0.10 mol / L PBS (pH=4.20) solution;
[0026] Figure 7The effect of different experimental conditions on the DPV response current ΔI: (A) ratio of template L-Glu to monomer 4,6-diaminoresorcinol, (B) number of polymerization cycles, (C) polymerization pH, (D) elution time, (E) detection pH;
[0027] Figure 8 :DPV response curves of MIP / MWCNTs / GCE to different concentrations of L-Glu (A) and the linear relationship curve between the peak current of L-Glu response and the concentration (B);
[0028] Fig. 9 This is a diagram showing the effect of interfering substances on the MIP / MWCNTs / GCE electrode.
[0029] Figure 1 Middle: 1. Silver / silver chloride electrode; 2. Platinum wire electrode; 3. Glassy carbon electrode; 4. Test solution; 5. Glassy carbon matrix; 6. MWCNTs film layer; 7. MIPs film layer; 8. L-Glu; 9. L-Glu three-dimensional structure cavity template. DETAILED DESCRIPTION
[0030] All reagents used in the examples were of analytical grade (AR), and all experimental water was ultrapure water (resistivity ≥ 18.3 MΩ·cm). In the following description, the descriptions of amino acids are all in English abbreviations.
[0031] 1. Experimental process
[0032] 1. Preparation of MWCNTs dispersion
[0033] 1.0 mg MWCNTs was placed in 1.0 mL NN dimethylformamide solution and ultrasonicated for 1 h to obtain MWCNTs dispersion (1.0 mg / mL).
[0034] 2. Preparation of electropolymerization primer
[0035] 0.5606 g of 4,6-diaminoresorcinol (monomer) and 0.1471 g of L-glutamic acid (template) were accurately weighed, dissolved in PBS buffer at pH = 5.0 and fixed to 100 mL to prepare a mixed liquid of 4,6-diaminoresorcinol (4.0 mM) and L-glutamic acid (1.0 mM), i.e., an electropolymerization base liquid with a molar concentration ratio of monomer to template of 4:1.
[0036] 3. Preparation of molecularly imprinted polymer film modified electrodes
[0037] The surface of the glassy carbon electrode (GCE, 3 mm in diameter) was polished into a mirror surface using 0.3 μm and 0.05 μm alumina powders, respectively, and then ultrasonically washed with anhydrous ethanol and ultrapure water for 5 min in sequence, and then dried for later use.
[0038] 5.0 μL of MWCNTs dispersion was dropped onto the surface of GCE and dried to obtain MWCNTs / GCE. MWCNTs / GCE was placed in 10.0 mL of electropolymerization base solution, and cyclic voltammetry was used to scan 23 cycles in the range of -0.2 to 2.0 V. The electrode was then placed in a formic acid / acetonitrile solution (V / V, 1:1) and eluted for 13 min to obtain a molecularly imprinted polymer modified electrode MIP / MWCNTs / GCE. The preparation process is as follows Figure 2 shown.
[0039] According to the above method steps, without adding MWCNTs, the other steps are the same as those for preparing the imprinted electrode modified with multi-walled carbon nanotubes, and the obtained imprinted electrode is MIP / GCE; at the same time, without adding MWCNTs and template molecules, the prepared electrode is NIP / GCE.
[0040] 4. L-Glu electrochemical detection
[0041] See also Figure 1 The surface-modified glassy carbon electrode 3 was used as the working electrode, the silver / silver chloride (containing saturated potassium chloride solution) electrode 1 was used as the reference electrode, and the platinum wire electrode 2 was used as the auxiliary counter electrode to construct a three-electrode system for measurement. 4- / 3- -0.20mol / L Na2SO4 solution, cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) tests were carried out; DPV test was carried out in 5.0mmol / L potassium ferrocyanide solution prepared by PBS solution (0.10mol / L) with pH = 4.2, and the DPV method was used to complete the detection of the response curve and linear relationship of the L-Glu concentration gradient (0.010, 0.050, 0.100, 0.500, 1.000, 5.000, 8.000, 10.00μM).
[0042] The surface-modified glassy carbon electrode 3 is the molecularly imprinted polymer film modified electrode in the L-glutamate detection sensor based on molecularly imprinted polymer film modified electrode of the present invention; the molecularly imprinted polymer film modified electrode comprises a glassy carbon matrix 5, the surface of the glassy carbon matrix 5 is modified with a MWCNTs film layer 6, the MWCNTs film layer 6 is loaded with a MIPs film layer 7, and the MIPs film layer 7 has a L-Glu molecule three-dimensional structure cavity 9. The sensor comprises a glassy carbon matrix 5 with a thickness of 1.0 to 5.0 mm, an acidified MWCNTs film layer 6 with a thickness of 20 to 200 nm, a MIPs film layer 7 with a thickness of 10 to 100 nm, and a L-Glu molecule three-dimensional structure cavity 9 with a diameter of 1 to 10 nm.
[0043] The standard addition method was used to detect L-Glu in the porcine serum sample (sample 4). The porcine blood samples were from three-way hybrid piglets (weight 10-15 kg) bred by the Institute of Subtropical Agriculture Ecology, Chinese Academy of Sciences (Changsha). 5.0 mL of porcine blood was taken from each pig, centrifuged at 4500 r / min for 15 min, and the supernatant was placed in a 5 mL glass centrifuge tube. This was repeated three times, and the supernatant was placed in a glass tube and stored at 4 ° C for later use. Six different porcine serum samples (10.00 μL) were added to a PBS buffer solution (0.10 mol / L, 9.990 mL) with a pH of 4.2, and the PBS solution contained a 5.0 mmol / L potassium ferricyanide solution. Different concentrations of L-Glu (0.200, 0.400, 0.600, 0.800, 1.000, 1.200 μM) were added to the porcine serum sample solution, and the DPV method was used for determination.
[0044] 2. Experimental Results and Analysis
[0045] 1. Characterization of materials and imprinted electrodes
[0046] 1.1 Morphological characterization
[0047] Scanning electron microscopy (SEM) was used to characterize the surface morphology of MWCNTs, NIP / MWCNTs / GCE, and MIP / MWCNTs / GCE. Figure 3 As shown. Figure 3 (A) It can be seen that MWCNTs have a long network structure, which increases the specific surface area. Figure 3 (B) and (C) are the electrode surface morphologies with and without the addition of imprinted molecule Glu, respectively. Comparison shows that the surface of MIP / MWCNTs / GCE is rougher and has many holes, indicating that an imprinted electrode was obtained after the addition of Glu template molecules.
[0048] Figure 4 A, B, and C are transmission electron microscopy (TEM) characterization images of MWCNTs, NIP / MWCNTs, and MIP / MWCNTs, respectively. Figure 4 (A) It can be seen that the MWCNTs structure is in the form of intertwined tubular structures, which are composed of NIP / MWCNTs ( Figure 4 B) and MIP / MWCNTs( Figure 4 C) TEM shows that a dense organic film is attached to the electrode surface, and Figure 4 C and Figure 4 Compared with Figure 1B, the particles attached to the electrode surface are smaller and have a network of holes, indicating the presence of an imprinted molecular membrane structure in the polymer matrix.
[0049] 1.2 Electrochemical characterization
[0050] The electrochemical characterization of the imprinted electrode preparation process was carried out using cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). Figure 5 (A) and (B) are bare electrode and different modified electrodes in 2.0 mM [Fe(CN)] 4- / 3- -CV and EIS diagrams in 0.20M Na2SO4 solution. Figure 5 (B) The inset is a local enlarged view.
[0051] Figure 5 In (A), GCE (curve a) shows an oxidation peak and a reduction peak at 0.141 V and 0.219 V, respectively. The redox peak currents of the MWCNTs / GCE electrode (curve b) modified with MWCNTs increase simultaneously, corresponding to Figure 5 The impedance value of curve b in (B) decreases because the mesh structure of MWCNTs increases the surface area of the electrode, increases the electronic conductivity, and increases the sensitivity, indicating that MWCNTs have been successfully modified to the electrode surface. The redox peak current of the MIP / MWCNTs / GCE electrode (curve c) with polymerized imprinted membrane decreases significantly and is almost a straight line, corresponding to Figure 5 The impedance value of curve c in (B) increases greatly because a dense organic film is formed on the electrode surface, which greatly hinders the transfer of electrons. The peak current of MIP / MWCNTs / GCE (curve d) increases again after elution, corresponding to Figure 5 The resistance value of curve d in (B) decreases significantly because many holes are left on the electrode surface after elution, which is conducive to the transfer of electrons and improves the conductivity, indicating that the imprinted electrode was successfully prepared in the experiment.
[0052] 2. Electrochemical behavior of L-Glu
[0053] Differential pulse voltammetry (DPV) was used to investigate the effect of different electrodes on the -5 mol / L L-Glu potassium ferrocyanide-PBS solution (5.0mmol / L [Fe(CN)] 4- / 3- -0.10mol / L PBS, pH=4.20). Figure 6As shown, GCE (curve a) generates a peak current at 0.212V. Since L-Glu is not electrically active, the peak current is generated by the oxidation of Fe(II) ions. The peak current of MWCNT / GCE (curve b) is larger than that of GCE, indicating that MWCNTs can increase the conductivity of the electrode and increase the electron transfer rate, but this electrode cannot produce a catalytic effect on L-Glu, so it is impossible to detect L-Glu. The peak current of NIP / GCE (curve c) is almost zero because a non-conductive organic film is polymerized on the surface of the electrode, which greatly hinders the transfer of electrons, so it is impossible to detect L-Glu. The peak current of MIP / GCE (curve d) is increased compared with curve c because many holes are left after the imprinted polymer is eluted, which increases the transfer of electrons. It is lower than curve a because the adsorption of holes on L-Glu hinders the transfer of Fe(II) ions on the electrode surface. When the concentration of L-Glu is greater, the response peak current will decrease accordingly. Therefore, MIP / GCE can detect L-Glu, but the single molecular imprinting sensor has poor conductivity and cannot achieve sensitive detection of L-Glu. The peak current of MIP / MWCNTs / GCE (curve e) is higher than that of curve d, and the peak potential is shifted to the right, indicating that MWCNTs not only have good conductivity, but also have an electrocatalytic effect, which increases the sensitivity of the sensor. In summary, the MIP / MWCNTs / GCE electrode used in the present invention can achieve rapid and sensitive detection of L-Glu.
[0054] 3. Condition optimization
[0055] 3.1. Optimization of template and monomer ratio
[0056] The ratio of template molecule to monomer affects the affinity and binding ability of molecular imprinted polymers, so it is necessary to optimize the ratio of template to monomer. The concentration of template molecule (L-Glu) was fixed at 10.0mmol / L, the concentration of monomer (4,6-diaminoresorcinol) was changed, and solutions with different ratios were prepared to prepare imprinted electrodes. The DPV method was used to detect 1.000×10 -5 mol / L L-Glu. Figure 7 As shown in Figure A, when the molar concentration ratio of template to monomer is 1:4, the difference (ΔI) between the detection peak current and the blank peak current is the largest. When the ratio is less than 1:4, insufficient effective binding sites are formed, which is not conducive to the adsorption of L-Glu. When the ratio is too large, the formed holes will be covered, reducing the effective binding sites. Therefore, the optimal template to monomer ratio is 1:4.
[0057] 3.2、Optimization of the number of aggregation circles
[0058] The thickness of the polymer film affects the detection sensitivity of the electrochemical sensor, and the thickness of the film is mainly affected by the number of scans. -5 The response curve of mol / L L-Glu is as follows Figure 7 As shown in Figure B, when the number of scanning circles increases, the peak current difference (ΔI) also increases. This is because the more scanning circles, the thicker the electrode surface film, and the more sufficient the L-Glu recognition sites provided. However, when the number of scanning circles is greater than 23, ΔI begins to decrease slowly. This is because when the surface film is too thick, mass transfer resistance will be generated, which is not conducive to the binding of L-Glu. Therefore, the optimal number of polymerization circles is 23.
[0059] 3.3. Optimization of pH of electropolymerization base solution
[0060] The pH of the electropolymerization solution affects the structure and function of molecular imprinting polymers. The electrodes formed by polymerization at different pH values detected 1.000×10 -5 The response curve of mol / L L-Glu is as follows Figure 7 As shown in C, when pH = 5.0, ΔI is the largest because L-Glu is an acidic amino acid with an isoelectric point of 3.22. When pH is 5.0, L-Glu is electronegative, which is more conducive to combining with monomer molecules. Therefore, the pH of the optimal electropolymerization base solution is 5.0.
[0061] 3.4. Elution time optimization
[0062] The elution time has an important influence on the formation of the imprinted electrode film. Using formic acid / acetonitrile (1:1) as the elution solution, the electrodes prepared under the same conditions were used to detect 1.000×10 -5 mol / L L-Glu. The results are as follows Figure 7 As shown in Figure D, when the elution time gradually increases, ΔI also increases. When the elution time is greater than 13 minutes, ΔI begins to decrease. This is because as the elution time increases, L-Glu will detach from the polymer membrane and form more holes. However, too long an elution time will destroy the structure of the imprinted membrane. Therefore, the optimal elution time is 13 minutes.
[0063] 3.5. Optimization of detection pH
[0064] The pH control of the L-Glu detection system solution has an important influence on the sensitive response of the sensor. The DPV method was used to examine the detection of L-Glu (1.000×10 -5 mol / L) of the oxidation peak current curve and pH, the results are as follows Figure 6As shown in E, when pH = 4.2, ΔI is the largest. This is because pH affects the charge properties of L-Glu and MIP / MWCNTs imprinted membrane. When the pH is too small or too large, it is not conducive to the adsorption of L-Glu. Therefore, the optimal detection system pH is 4.2.
[0065] 4. Detection range and detection limit
[0066] Under the optimized conditions, the MIP / MWCNTs / GCE electrode was used to detect different concentrations of L-Glu in a 5.0 mmol / L potassium ferrocyanide solution prepared by PBS buffer (0.10 mol / L, pH = 4.20) by DPV method. The results are shown in Figure 8 As shown. Figure 8 (A) It can be seen that the peak current of DPV response decreases with the increase of L-Glu concentration. Figure 8 (B) It can be seen that the difference between the response peak current and the blank peak current (ΔI) and the logarithm of the L-Glu concentration in the range of 0.010 to 10.00 μmol / L have a good linear relationship, and the linear equation is y = -4.6199lgC + 39.943, R 2 =0.9926, the detection limit is 5.130×10 -9 mol / L (S / N=3). The present invention is compared with other molecular imprinting sensors (see Table 1). The detection limit of the present invention is lower than that of the L-Glu molecular imprinting sensor reported in the literature. On the one hand, it may be because the monomer 4,6-diaminoresorcinol used in the present invention has more molecular imprinting binding sites than the o-aminophenol used in the literature, and on the other hand, it is because MWCNTs improve the detection sensitivity of the sensor. Compared with other literature, the enzyme-free sensor prepared by the present invention has excellent performance, superior linear range and detection limit.
[0067] Table 1 Performance comparison of different electrodes responding to L-Glu
[0068] Table 1Comparison of performance with different modified electrodes for L-Glu.
[0069]
[0070] Note: GLOx: Glutamate Oxidase; Gldh: Glutamate dehydrogenase; PEI: polyethyleneimine; MWCNTs: multi-walled carbon nanotubes; MIP: molecular imprinted polymer; PPD: poly(m-phenylenediamine); PDE: platinum disc electrode; CPE: carbon paste electrode.
[0071] The relevant references mentioned in Table 1 are as follows:
[0072]
[29] Freya O.,Holtzman T.,McNamara RM,Theobald DEH,Wal PD,RooijN.F.,Dalley JW,Biosens.Bioelectron.,2010,26(2),477-484.
[0073]
[30] Liang B., Zhang S., Lang QL, Song JX, Han LH, Liu AH, Anal.Chim.Acta, 2015, 884(16), 83-89.
[0074]
[33] RE,Cristina L.,Mallikarjunarao G.,Leiter JC,Biosens.Bioelectron.,2014,52(15),397-402.
[0075]
[41] Zhao S., Cui LF, Shen Q., Environmental Science & Technology, 2012, 35(11), 70-74.
[0076]
[47] Borisova T.,Kucherenko D.,Soldatkin O.,Kucherenko I.,PastukhovA.,Nazarova A.,Galkin M.,Anal.Chim.Acta,2018,1022(31),113-123.
[0077]
[48] Song JX,Liang B.,Han DF,Tang XJ,Lang QL,Feng RR,HanL.H.,Liu AH,Enzyme Microb.Technol.,2015,70,72-78.
[0078]
[49] Gomes SP, Couto CMCM, Montenegro MCBSM, J. Anal. Chem., 2013, 68(9), 794-800.
[0079]
[50] Azmi NE,Ahmad M.,Abdullah J.,Sidek H.,Heng LY,Anal.Biochem.,2009,388(1),28-32.
[0080]
[51] Maalouf R.,Chebib H., Y.,Vittori O.,Sigaud M.,Biosens.Bioelectron.,2007,22(11),2682-2688.
[0081] 5. Reproducibility, repeatability and stability of electrodes
[0082] Five electrodes were prepared from the same batch and the same electrode was used for multiple tests with a concentration of 1.000×10 -5 mol / LL-Glu, the peak current deviations were 3.51% and 2.36%, respectively, indicating that the electrode prepared by this method has good reproducibility and stability. In order to explore the stability of the electrode, the prepared electrode was stored at room temperature and the concentration of 1.000×10 -5 mol / L L-Glu was detected once by DPV method. After 30 consecutive days of measurement, the response current of the electrode decreased by 7.80% compared with the initial value, indicating that the electrode has good stability and service life.
[0083] 6. Anti-interference
[0084] The DPV method was used to examine the interference of some common amino acids on the determination of L-Glu. The interference substances with a concentration of 50 times (5.000×10 -4 mol / L) alone and with L-Glu (1.000×10 -5 mol / L) when mixed, the response peak current is as follows Fig. 9 As shown. Fig. 9It can be seen that L-aspartic acid (L-Asp), L-tryptophan (L-Trp), L-tyrosine (L-Tyr), L-lysine (L-Lys), L-arginine (L-Arg), L-histidine (L-His), L-glycine (L-Gly), L-cysteine (L-Cys), and L-threonine (L-Thr) will not interfere with the detection of L-Glu, indicating that the electrode has good selectivity.
[0085] 7. Actual sample testing
[0086] The pretreated porcine serum samples were taken, and the prepared molecular imprinting electrode MIP / MWCNTs / GCE was compared with the results measured by the high performance liquid chromatography analyzer. The results are shown in Table 2. It can be seen that the results obtained by this method are consistent with those obtained by the high performance liquid chromatography method, and the relative error is less than 5.0%, indicating that this method has good accuracy. The porcine serum samples were measured by the spike recovery method. 10.00 μL of the porcine serum sample was taken in 9.990 mL of potassium ferricyanide solution prepared by PBS buffer, and then different concentrations of standard L-Glu were added for detection and the recovery rate was calculated. The results are shown in Table 3. The recovery rate is 97.4% to 105.5%, indicating that the electrode can be used for the detection of actual samples.
[0087] Table 2 Comparison of different methods for the detection of L-Glu in pig serum samples
[0088] Table2Comparison of different methods for detection of L-Glu inpiglet serum samples (n=6)
[0089]
[0090] Table 3 Application of MIP / MWCNTs / GCE in the detection of L-Glu in pig serum samples
[0091] Table3 Application of MIP / MWCNTs / GCE to determination of L-glu inpiglet serum samples (n=6)
[0092]
[0093] The present invention prepares a L-Glu molecular imprinting sensor (MIP / MWCNTs / GCE), which has a good recognition effect on L-Glu and a good linear response relationship, with a detection limit of 5.130×10 -9mol / L. At the same time, the sensor has good selectivity, strong reproducibility and high stability. It can be used for the sensitive detection of L-Glu in pig serum samples, providing a new way for the detection of glutamate and has important application prospects in the field of life sciences.
Claims
1. A method for detecting L-glutamic acid based on a molecularly imprinted polymer film modified electrode, characterized in that: The method comprises the following steps: (1) Preparing a MWCNTs dispersion: placing MWCNTs in a NN dimethylformamide solution, and obtaining a MWCNTs dispersion after ultrasonic treatment, wherein the concentration of MWCNTs in the MWCNTs dispersion is 0.5 to 2.0 mg / mL; (2) preparing an electropolymerization base solution: dissolving 4,6-diaminoresorcinol and L-glutamic acid in a PBS buffer solution at a pH of 4.0 to 5.5, and preparing a mixed liquid of 4,6-diaminoresorcinol and L-glutamic acid, i.e., the electropolymerization base solution, wherein the molar concentration ratio of 4,6-diaminoresorcinol to L-glutamic acid in the electropolymerization base solution is (2 to 6):1, and the concentration of the PBS buffer solution in the electropolymerization base solution is 0.01 to 0.20 mol / L; (3) Preparation of molecular imprinted polymer modified electrode: polish the surface of glassy carbon electrode, clean it with ultrasonic wave and air dry it, apply MWCNTs dispersion droplets to the surface of glassy carbon electrode, dry it and obtain MWCNTs / GCE, place MWCNTs / GCE in electropolymerization base solution, scan for 20 to 30 cycles in the range of -0.2 to 2.0 V by cyclic voltammetry, then place the electrode in formic acid / acetonitrile solution and elute for 10 to 20 min to obtain molecular imprinted polymer modified electrode MIP / MWCNTs / GCE; the volume ratio of formic acid to acetonitrile in the formic acid / acetonitrile solution is (0.5 to 4):1; (4) A three-electrode system was constructed using molecular imprinting polymer film modified electrode MIP / MWCNTs / GCE as the working electrode, a silver / silver chloride electrode as the reference electrode, and a platinum wire electrode as the counter electrode. Cyclic voltammetry and electrochemical impedance spectroscopy were then used to investigate the electrochemical behavior of L-glutamate on different modified electrodes. Differential pulse voltammetry was used to test L-glutamate at different concentrations, and a working standard curve was drawn. The standard addition method was then used to detect L-glutamate in the test samples.
2. The method according to claim 1, characterized in that In step (3), the surface of the glassy carbon electrode is polished using 0.3 μm and 0.05 μm alumina powders, respectively.
3. The method according to claim 1, characterized in that The diameter of the glassy carbon electrode in step (3) is 3 mm. 5 μL of MWCNTs dispersion is dropwise coated on the surface of the glassy carbon electrode and dried to obtain MWCNTs / GCE. The MWCNTs / GCE is placed in 10 mL of electropolymerization base solution.
4. The method according to claim 1, characterized in that In step (4), the reaction mixture was heated to 2.0 mmol / L [Fe(CN)] 4- / 3- The electrochemical behavior of L-glutamic acid on different modified electrodes was investigated by cyclic voltammetry and electrochemical impedance spectroscopy in 0.20 mol / L Na2SO4 solution. In a potassium ferrocyanide solution for detection prepared from a PBS buffer solution for detection, different concentrations of L-glutamic acid are tested by differential pulse voltammetry, a working standard curve is drawn, and then the L-glutamic acid in the sample to be tested is detected by the standard addition method; the concentration of the PBS buffer solution for detection is 0.01-0.20 mol / L, the pH of the PBS buffer solution for detection is pH3.7-4.4, and the concentration of the potassium ferrocyanide solution for detection is 1.0-10.0 mmol / L.
5. A L-glutamate detection sensor based on molecular imprinting polymer film modified electrode, characterized in that: The sensor comprises a molecular imprinting polymer film modified electrode as a working electrode; the molecular imprinting polymer film modified electrode comprises a glassy carbon matrix (5), the surface of the glassy carbon matrix (5) is modified with a MWCNTs film layer (6), the MWCNTs film layer (6) is loaded with a MIPs film layer (7), and a L-Glu molecular three-dimensional structure cavity (9) exists on the MIPs film layer (7).
6. The sensor according to claim 5, characterized in that The sensor comprises a glassy carbon matrix (5) having a thickness of 1.0 to 5.0 mm, a MWCNTs film layer (6) having a thickness of 20 to 200 nm, a MIPs film layer (7) having a thickness of 10 to 100 nm, and a L-Glu molecular three-dimensional structure cavity (9) having a diameter of 1 to 10 nm.
7. The sensor according to claim 5 or 6, characterized in that The sensor has a good linear relationship with the concentration of L-glutamic acid, and the linear range of detection is 1.00×10 -8 ~1.00×10 -5 mol / L, the detection limit is 5.13×10 -9 mol / L.
Citation Information
Patent Citations
L-glutamic acid detection sensor based on molecularly imprinted polymer membrane modified electrode
CN211122646U